La terapia lúdica y el desarrollo de la motricidad fina en los niños y niñas con parálisis cerebral infantil de 7 - 10 años de edad que asisten al centro de atención y desarrollo de niños/as y adolescentes especiales de la ciudad de Loja. período febrero- septiembre de 2014 - Orellana Fierro, Nydia Enriqueta (2015)
This research paper entitled: PLAY THERAPY AND FINE MOTOR DEVELOPMENT IN CHILDREN WITH CEREBRAL PALSY CHILDREN AGED 7-10 ATTENDING THE CENTER OF ATTENTION AND DEVELOPMENT OF CHILDREN / AND TEENAGERS AS SPECIAL LOJA, It is to analyze the influence of the play therapy on fine motor skills of children aged 7-10 years of age with infantile cerebral palsy. Being investigated to establish the age of the development of fine motor skills and playful technique used by professionals in order to develop a plan for improving fine motor skills. The research was conducted with a correlational methodology, where not only was limited to data collection, but also to identify the relationship between two variables, play therapy and the development of fine motor skills, he worked with a sample 7 children from the center. The above favored the formulation of conclusions and recommendations, which indicate that the level of development of fine motor skills of children of 7-10 years old with cerebral palsy corresponds to an age of one year three months, demonstrating delay of up to seven years for chronological age, too, was evident that professionals apply the playful art of body language and movement, it is not conducive to a good motor development, so it is recommended that the authorities of center, manage ongoing training on play therapy and resources needed to cater center professionals.